Clinicopathological and treatment analysis of 13 extragastrointestinal stromal tumors of mesentery and retroperitoneum - Iqbal, Nida (Ann Gastroenterol, 2015)
BACKGROUND: Extragastrointestinal stromal tumors (EGISTs) are extremely rare mesenchymal tumors histologically and immunophenotypically similar to GI stromal tumors (GISTs). The aim of this study was to analyze the clinicopathological factors and treatment outcome in 13 patients with EGISTs treated at a tertiary care center. METHODS: Of 109 patients with GISTs treated at our center between April 2002 and December 2012, 13 patients with EGISTs were analyzed for clinicopathological factors and treatment outcome. RESULTS: Mean age was 45.8 (range 30-61) years, and females constituted 62% with a male:female ratio of 0.6:1. The most common tumor sites were mesentery in 10 patients and retroperitoneum in 3 patients. Mean tumor size was 11.7 (range 5-18) cm. Four (31%) patients were metastatic at presentation, the most common site of metastases being the liver in 3 (75%) patients. Lymph node enlargement was seen in 2 patients. Surgery was performed in 8 (62%) patients, 7 with localized disease, and 1 with metastatic disease. R0 resection was achieved in 3 (38%) patients. Five (71%) patients were considered as high-risk. Recurrences were seen in 3 patients (patient 3, 5 and 13) with localized disease after surgical resection, at 18, 7 and 137 months, respectively. At the last follow up, 7 patients were alive and 6 died of disease progression. The median overall survival was 34 (7-148) months. CONCLUSIONS: EGISTs present at a younger age in the developing than in the developed countries. Females are more commonly affected than males. Lymph node metastases may be commonly present.